2007
DOI: 10.1007/s10905-007-9078-z
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory versus Contact Cues in Host Plant Recognition of a Monophagous Chrysomelid Beetle

Abstract: Abstract. The importance of olfactory versus contact cues for host plant recognition was investigated in the tortoise beetle Cassida canaliculata Laich. (Coleoptera: Chrysomelidae), which is strictly monophagous on meadow sage. The reaction of adult beetles to olfactory and contact host cues was tested using three bioassays (locomotion compensator, six-chamber-olfactometer, 'stem arena') to account for different behavioral contexts. Bioassay-guided fractionation of plant extracts was elaborated to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 64 publications
2
31
1
2
Order By: Relevance
“…This confirms our previous laboratory results, which showed that C. canaliculata is able to recognise its host, S. pratensis, using contact cues (Heisswolf et al, 2007). Still, it is no sufficient proof for host plant recognition from a distance.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This confirms our previous laboratory results, which showed that C. canaliculata is able to recognise its host, S. pratensis, using contact cues (Heisswolf et al, 2007). Still, it is no sufficient proof for host plant recognition from a distance.…”
Section: Discussionsupporting
confidence: 88%
“…In summary, this study shows that C. canaliculata is able to recognise its host plant, S. pratensis, from a distance, although a previous laboratory study gave no such indication (Heisswolf et al, 2007). Thus, the analysis of movement patterns in a seminatural arena seems to be a useful way of discovering behavioural responses to host plant cues that could not be detected with standard laboratory methods.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The latency period (i.e., time taken before a 233 stem was chosen), (Heisswolf et al, 2007), was analysed by one-way ANOVA, and 234 again was partitioned into gender-wise categories. (Fig.…”
Section: Procedures 129mentioning
confidence: 99%